2014
DOI: 10.1210/en.2014-1266
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Programming: Prenatal Steroid Excess Disrupts Key Members of Intraovarian Steroidogenic Pathway in Sheep

Abstract: Prenatal testosterone (T) excess disrupts ovarian cyclicity and increases circulating estradiol levels as well as follicular recruitment and persistence culminating in multifollicular ovary similar to women with polycystic ovary syndrome. We tested whether prenatal T excess, by androgenic or estrogenic action, disrupts the steroid biosynthetic machinery in sheep in a cell-, follicle stage-, age-, and treatment-specific manner consistent with the ovarian disruptions and increased estradiol release. Impact of T/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 63 publications
3
21
0
Order By: Relevance
“…Intrauterine programming has been proposed as one of the plausible mechanisms that cause PCOS, as evidenced by the high heritability of the disease and animal models demonstrating that prenatal exposure to high levels of androgens or AMH results in the acquisition of the PCOS phenotype in the offspring (Filippou & Homburg 2017, Tata et al 2018. To date, several studies have been conducted in prenatal androgenized sheep and monkeys in which a PCOS phenotype was observed during adulthood, which, in turn, has been related to DNA methylation changes in the case of monkeys (Manikkam et al 2006, Abbott et al 2008, Veiga-Lopez et al 2008, 2012, Smith et al 2009, Ortega et al 2010, Xu et al 2011, Padmanabhan et al 2014, Puttabyatappa et al 2018. Nevertheless, little…”
Section: Dna Methylation In the Peripheral And Cord Blood From Women mentioning
confidence: 99%
See 2 more Smart Citations
“…Intrauterine programming has been proposed as one of the plausible mechanisms that cause PCOS, as evidenced by the high heritability of the disease and animal models demonstrating that prenatal exposure to high levels of androgens or AMH results in the acquisition of the PCOS phenotype in the offspring (Filippou & Homburg 2017, Tata et al 2018. To date, several studies have been conducted in prenatal androgenized sheep and monkeys in which a PCOS phenotype was observed during adulthood, which, in turn, has been related to DNA methylation changes in the case of monkeys (Manikkam et al 2006, Abbott et al 2008, Veiga-Lopez et al 2008, 2012, Smith et al 2009, Ortega et al 2010, Xu et al 2011, Padmanabhan et al 2014, Puttabyatappa et al 2018. Nevertheless, little…”
Section: Dna Methylation In the Peripheral And Cord Blood From Women mentioning
confidence: 99%
“…These molecular and morphological changes in the ovarian tissue could be attributed to epigenetic alterations as proposed in animal models of PCOS. Predominantly, studies have reported that prenatal testosterone treatment in sheep results in an increase in the occurrence of persistent and growing follicles (contributing to the morphology of a PCO), luteal and antral follicles defects, a decline in primordial follicles and an altered ovarian protein content of AMH, ovarian steroidogenic enzymes, matrix metalloproteases and proteins related to insulin pathway during adulthood (Manikkam et al 2006, Veiga-Lopez et al 2008, 2012, Smith et al 2009, Ortega et al 2010, Padmanabhan et al 2014, Puttabyatappa et al 2018. Remarkably, this fetal programming induced by prenatal testosterone correlates with defects in the expression of ovarian steroidogenic genes and miRNAs associated with insulin pathway in the ovaries of fetal ewes (Luense et al 2011).…”
Section: Dna Methylation In the Ovarian Tissue And Granulosa Cells Frmentioning
confidence: 99%
See 1 more Smart Citation
“…The thecal androgen production could also be influenced by LH hypersecretion [44, 45, 96]. Although the reduced expression of the enzyme CYP17A1 in the theca interna of antral follicles in prenatal T-treated sheep [97] is inconsistent with hyperandrogenism, this may be offset by an increase in the activity of this enzyme, compensatory induction of another isoform, or autocrine/paracrine feedback inhibition [97, 98]. However, gestational T increases AR in these follicles supporting functional hyperandrogenism [39].…”
Section: Ovarian Disruptionsmentioning
confidence: 99%
“…Foetal gonads are already able to produce and secrete steroid hormones, which are important for the foetal programming of sexual development and reproductive function, for example the development of internal and external genitalia (Kucinskas & Just, ; Padmanabhan, Salvetti, Matiller, & Ortega, ). In steroid biogenesis, many enzymes are engaged (Miller, ); the pathway for reproductive steroid hormone synthesis and the enzymes involved are delineated in Figure .…”
Section: Introductionmentioning
confidence: 99%